Orchestrating Multi-Agent Knowledge Ecosystems: The Role of Makerspaces - Shi, Jia-Lu; Chen, Guo-Hong (Frontiers in Psychology, 2022)
An innovation ecosystem consists of multiple agents and emerges as knowledge networks for symbiotic and sustainable growth. The existing research on multi-agents knowledge interaction has focus on university-industry-government collaboration. In response to a national strategy of “mass entrepreneurship and innovation for all” in China, the number of makerspaces rose to the top of the world by the end of 2017. Makerspaces play central roles of network orchestrator, knowledge intermediary, and knowledge gatekeeper in the innovation ecosystem. Most previous research on makerspaces is concerned with the internal value co-creation among makers or startups and offers few studies on external knowledge creation from the perspective of innovation ecosystem. With the fast-developing emerging industries, global warming environment and shared economy, this paper adds the fourth helix of civil society and the fifth helix of natural environment based on Quintuple Helix model to key agents in the innovation ecosystem. Therefore, we adopts the methods of in-depth interviews and surveys to develops a multi-levels and multi-agents conceptual framework from macro, meso, and micro perspective. Based on the framework we elaborate the roles, functions, and activities of each agent and explore how makerspaces can orchestrate knowledge networks to enhance collaboration for innovation among different agents. Three important attributes of the multi-level model are described from the biological perspective as follows: multi-levels ecological balance, multi-agents helical interplay, and multi-stages knowledge orchestration. In particular, this model facilitates Quintuple Helix model to analyze the five subsystems (political subsystem, educational subsystem, economic subsystem, civil society, and natural environment) which populate an innovation ecosystem in the process of knowledge exchange, knowledge coordination, knowledge cooperation, and knowledge orchestration. Thus, this paper can help policymakers, researchers and managers to take a systems approach for sustainable development jointly.